Overview Biodiesel-hydrogen as a combined fuel resource in dual fuel diesel engine - Ahmad Khoirur Roziqi; Bambang Sudarmanta (International Journal of Marine Engineering Innovation and Research, 2025)
Rising concerns about energy consumption and the environmental impact of fossil fuels are driving the search for alternative, cleaner energy sources. Extensive research has been conducted to explore alternative fuels as a means of optimizing energy requirements. This review provides a comprehensive analysis of how alternative fuels affect the combustion process in compression ignition (CI) engines, focusing on various combinations of diesel fuel with biodiesel, hydrogen, ammonia, LPG, and CNG. These fuels were combined to determine the most effective option. In the case of biodiesel-hydrogen mixtures, a 13-22% decrease in brake thermal efficiency (BTE) was observed. Conversely, using natural gas as an alternative fuel in dual-fuel engines resulted in a substantial increase in brake specific fuel consumption (BSFC), reaching up to 250 g/kWh.